2017
DOI: 10.1038/srep42888
|View full text |Cite
|
Sign up to set email alerts
|

Cbx3/HP1γ deficiency confers enhanced tumor-killing capacity on CD8+ T cells

Abstract: Cbx3/HP1γ is a histone reader whose function in the immune system is not completely understood. Here, we demonstrate that in CD8+ T cells, Cbx3/HP1γ insufficiency leads to chromatin remodeling accompanied by enhanced Prf1, Gzmb and Ifng expression. In tumors obtained from Cbx3/HP1γ-insufficient mice or wild type mice treated with Cbx3/HP1γ-insufficient CD8+ T cells, there is an increase of CD8+ effector T cells expressing the stimulatory receptor Klrk1/NKG2D, a decrease in CD4+ CD25+ FOXP3+ regulatory T cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Additionally, NK and NKT cells are sensitive to various inhibitory molecules within the TME ( 93 ). Moreover, we show that the frequency of NK and NKT cells in NB tumors is low, and no differences are detected in tumors from wt or Cbx3 /HP1γ-deficient mice yet NB tumor growth is greatly abrogated in Cbx3 /HP1γ-deficient mice ( 70 ). Our findings imply that NK or NKT cells may not play an important role in controlling NB tumor growth.…”
Section: Adoptive Nk- and Natural Killer T (Nkt)-cell Therapymentioning
confidence: 84%
See 1 more Smart Citation
“…Additionally, NK and NKT cells are sensitive to various inhibitory molecules within the TME ( 93 ). Moreover, we show that the frequency of NK and NKT cells in NB tumors is low, and no differences are detected in tumors from wt or Cbx3 /HP1γ-deficient mice yet NB tumor growth is greatly abrogated in Cbx3 /HP1γ-deficient mice ( 70 ). Our findings imply that NK or NKT cells may not play an important role in controlling NB tumor growth.…”
Section: Adoptive Nk- and Natural Killer T (Nkt)-cell Therapymentioning
confidence: 84%
“…Our recent studies suggest that such an approach is attainable. We show that by targeting the histone reader Cbx3 /HP1γ, we can enhance the tumor killing capacity of effector CD8 + T cells ( 69 , 70 ). As a result, adoptive transfer of Cbx3 /HP1γ-deficient CD8 + effector T cells alone into wild type (wt) tumor-bearing mice greatly reduces NB growth.…”
Section: Adoptive T-cell Therapy (Act)mentioning
confidence: 92%
“…In addition, CBX3/HP1γ was demonstrated to have novel function in the epigenetic regulation of both cell differentiation and cancer development in various types of cancers ( 10 ). In particular, Michael Su et al found that reducing the levels of Cbx3/HP1γ could enhance tumor-killing capacity on CD8+ T cells ( 32 ). Taken these findings together, we suppose that Cbx3/HP1γ serve as not only a novel cancer biomarker of high value in diagnosis and prognosis, but also an effective target for gene therapy against various human cancers.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, many different approaches exist, which do not fullfill this set of criteria. The vast majority of them, including DNA 8,9 -and RNA [10][11][12][13] -based PCR and reverse transcription quantitative real-time PCR (RT-qPCR), species-specific transcriptome [14][15][16][17][18][19][20] and proteome 21,22 analyses as well as flow cytometry [23][24][25] , are molecular profiling approaches which require tissue dissociation or lysis and do not address host contribution in situ on a single cell level. To investigate the unperturbed interaction between the tumor and its microenvironment, the use of genetically modified cells or mouse models expressing fluorescent reporter proteins [26][27][28][29][30] might want to be avoided.…”
Section: Comparison With Existing Approachesmentioning
confidence: 99%